Progress of Research on Urban Growth Boundary and Its Implications in Chinese Studies Based on Bibliometric Analysis - Liu, Xiaoyang; Shi, Weihao; Zhang, Sen (International journal of environmental research and public health, 2022)
Urban sprawl is a development theme of cities all over the world, especially in developing countries with rapid urbanization, and the long-established rough and outward urban growth pattern has brought about a series of social and ecological problems. As an important tool in controlling urban sprawl in western countries, the urban growth boundary (UGB) has become one of the three major policy tools in the national spatial planning system since it was introduced into China. Combined with a bibliometric analysis, this literature review summarizes UGB studies on development and evolution, delimitation means, and implementation management and provides references for studying UGB adaptability in China. The results show that: (1) Originating from Howard’s garden city concept, UGB studies have formed a relatively complete system of “theoretical basis, technical methods, supporting policies, and implementation management” through long-term empirical research in foreign countries. With a relatively late start in China, UGB research currently focuses on different situations between China and abroad and the adaptation of China’s localization. (2) UGB delimitation mainly includes two aspects: forward expansion, which, from the urban development perspective, is mainly supported by cellular automata (CA) urban growth simulation; and reverse restriction, which, from the ecological protection perspective, is supported by ecological security pattern construction, ecological sensitivity evaluation, and land suitability evaluation. (3) Many foreign UGB implementations have different forms and more flexible and comprehensive corresponding supporting policies. However, the current state of research in China in this area is still insufficient. Against the background of the national spatial planning system reform, the findings of this review provide references for delineating UGB that considers ecological protection and urban development under the scenarios of planning, formulating a supporting mechanism for multi-subject participation and multi-party coordination, and establishing an adjustment system based on implementation effect evaluation.